Motor Development Embodied, Embedded, Enculturated, and Enabling. [article]. - Adolph, Karen E.
Motor development and psychological development are fundamentally related, but researchers typically consider them separately. In this review, we present four key features of infant motor development and show that motor skill acquisition both requires and reflects basic psychological functions. (a) Motor development is embodied: Opportunities for action depend on the current status of the body. (b) Motor development is embedded: Variations in the environment create and constrain possibilities for action. (c) Motor development is enculturated: Social and cultural influences shape motor behaviors. (d) Motor development is enabling: New motor skills create new opportunities for exploration and learning that instigate cascades of development across diverse psychological domains. For each of these key features, we show that changes in infants? bodies, environments, and experiences entail behavioral flexibility and are thus essential to psychology. Moreover, we suggest that motor development is an ideal model system for the study of psychological development. -- (from the author)